DIVAs: a multi-agent simulation framework. (29th April 2022) - Al-Zinati, Mohammad; Zalila-Wenkstern, Rym
DIVAs is a generic multi-agent-based simulation framework (MABS) for the development of simulation systems. In DIVAs, agents are situated in an open environment that is partially perceived, and the environment is totally decoupled from agents. DIVAs provides a set of reusable architectures, abstract and concrete classes, software components, and tools for the definition of agents and open environments, a microkernel for the management of the simulation workflow, domain-specific libraries for the rapid development of simulations, and reusable and extendable components for the control and visualisation of simulations. Also, DIVAs offers the means to dynamically access and modify agent and environment properties at run-time. This paper discusses the DIVAs' reference architecture and outlines its major design decisions.